Pengujian Black Box pada Aplikasi Sistem Informasi Pengelolaan Masjid Menggunakan Teknik Equivalence Partitions - Hendri, Hendri; Hasiholan Manurung, Jimmi Walter; Ferian, Rifqi Audi; Hanaatmoko, Wahyu Faharrudin; Yulianti, Yulianti (Program Studi Teknik Informatika Universitas Pamulang, 2020)
Black-box testing is very important because this technique is able to identify errors in functions, interfaces, data models, and access to external data sources. In implementation problems often arise when testers are never sure whether the software being tested has actually passed the test. This happens because there may be several execution paths that have never been tested. Testers must make every possible input data combination for testing. The selection of input data to find errors is a problem for testers because it has a high probability, so the test case design can automatically become a solution. In this implementation the application to be tested using black-box testing is the Mosque Management Information System. The Mosque Management application will be tested using black box testing where the test is only intended to see if the program matches the function desired by the program without knowing the program code used. To produce test case designs automatically in black box method software testing with equality partition technique. Equivalence Partitions technique is a test based on entering data on each form in the mosque management information system, each menu will be tested and grouped according to function whether it is valid or not.